Soil humus characteristics in virgin and cleared areas of the paraná river basin in Brazil - Nascimento, V. M. [UNESP]; Almendros, G.; Fernandes, F. M. [UNESP] (Elsevier, 1992)
A study of the characteristics and distribution of the soil humus fractions in representative ecosystems of central Brazil was carried out with special emphasis on the comparison between the soils under virgin vegetation-Cerrado-and those subjected to cultivation. In spite of the contrasted vegetation and cultural practices in the sites studied, the soil humus showed analogous characteristics: there was a negligible amount of plant residues, the humic and fulvic acids amounted to approximately 70% of the total organic carbon, and about 40% of these humic substances were in extremely stable association with the soil mineral fraction, the HCl-HF treatment being required for their extraction. The stability of such organo-mineral complexes increased slightly in the cultured sites. The study of the humic acid fraction showed increased oxidation and aromaticity in most of the cultivated sites: the lowest values for the IR alkyl vibrations and H/C atomic ratios and the highest ones for the optical density at 465 nm were observed in sites transformed into orchards, whereas the above changes were small in those used as pasture. The 14C NMR spectra confirmed that the proportion of polyalkyl structures decreased in the humic acids of soils subjected to cultivation, as opposed to that of carboxyl groups. In spite of the high stability inferred for the organic matter throughout the wide area examined, the samples from the original Cerrado as well as from those transformed into pastures showed, in laboratory conditions, higher mineralization rates than those from the sites subjected to cultivation. This is partly attributed to the decreased proportions of extractable humic substances in the latter. © 1992.
Keywords: cerrado; cultivation; forest clearing; fulvic acid; humic acid; humus; rain forest soil; Brazil, Parana River Basin